LIDAR OBSERVATIONS ABOVE NY-ALESUND, SVALBARD, NORWAY DURING WINTER 1995/96 - シライシ, コウイチ; フジワラ, モトオ; イワサカ, ヤスノブ; シバタ, タカシ; ナガタニ, マサヒロ; アダチ, ヒロシ; サカイ, テツ; フジノ, カズヒロ; SHIRAISHI, Kouichi; FUJIWARA, Motowo; IWASAKA, Yasunobu; SHIBATA, Takashi; et al. (National Institute of Polar Research, 1997)
P(論文) Lidar observations of stratospheric aerosols were performed in the winter of 1995/96 at Ny-Alesund, Svalbard in Norway (79°N, 12°E). Superposed on the usual aerosol layer, polar stratospheric clouds (PSCs) were observed intermittently between December 1995 and February 1996. The temperature at the heights of the PSCs was very low, below the estimated frost point of nitric acid trihydrate (NAT). PSC observed initially at the appearance of cold air always consisted of solid particles. Each height distribution of scattering ratio (R) and depolarization (δ) ratio has a single peak, and the relation between R and δ shows a positive correlation at the edge of the horizontal extent of the PSC layer. As the cold area developed, PSC layers with negative correlation between R and δ were frequently detected, as they had been in previous observations. departmental bulletin paper